Radicalizing community development: the changing face of the Queer Movement in Hyderabad City. (6th July 2017) - Kumar, Pushpesh
Abstract: Metropolitan cities in India have become a site of queer activism and queer visibility after the Delhi High Court decriminalized homosexuality in 2009. The Supreme Court through its 2013 verdict overruled the 2009 Delhi High Court judgement thereby recriminalising homosexuality. However, this conservative stance of the Supreme Court could not diminish the spirit of visibility and mobilizational politics. Queer aspirations seem to have intensified and multiplied in the age of social media. Hyderabad as one of the corporatized cities of India has experienced heightening of queer politics in recent years. The article delineates the growing radicalization of the queer movement in the city of Hyderabad since 2014/2015 due to the entry of a vocal and enlightened transleadership. The latter has attempted to remap and rescript Hyderabad's queer movement through decorporatization and greater inclusion of grass root issues in in its political mobilizations. Through its tactics and organizational approaches, it has also challenged the hegemonic constructions of queer politics as articulated by Non Governmental Organizations and elites within the gay community.